Pengembangan Jobsheet Pembelajaran Gambar Teknik dengan Autocad untuk Meningkatkan Minat Mahasiswa di Universitas Muhammadiyah Purworejo - Jatmoko, Dwi; Primartadi, Aci; Widiyatmoko; Nur Afif, Iqfan (Lentera: Jurnal Ilmiah Kependidikan, 2022)
This study aims to determine the feasibility of the AutoCAD Engineering Drawing learning Jobsheet which was developed to increase interest in learning and analyze how much the technical drawing competence increases in automotive engineering education students at Muhammadiyah University of Purworejo. This study uses a four-D model device development model with the research subjects taken are students of Automotive Engineering Education, University of Muhammadiyah Purworejo totaling 40 students with a sample of two class groups. Collecting data using a questionnaire method and quantitative data analysis test by taking a percentage of the research results. The results of the research show that: (1) the AutoCAD Jobsheet development procedure includes define, design, develop, disseminate searches. (2) Jobshet AutoCAD technical drawings are suitable for use as learning media. This can be proven from media and material experts who show a percentage of 90%. The AutoCAD engineering drawing jobsheet also meets the criteria very good. This is shown through student responses which include small group trials obtaining an average percentage of 69% and large group trials obtaining an average percentage of 77.56%. The results of the validation of media experts and material experts as well as the results of the small group test and large group test indicate that the module is feasible to use. Comparison of student learning interest in the experimental class and control class with a score of 77.56 experimental class and control class score of 68.25. Based on these results, the AutoCAD technical drawing Jobsheet can increase student interest in learning.